Sarason's Conjecture of Toeplitz Operators on Fock-Sobolev Type Spaces. (2nd May 2018) - Wang, Xiaofeng; Chen, Jianjun; Xia, Jin
Abstract : In this note, we will solve Sarason's conjecture on the Fock-Sobolev type spaces and give a well solution that if Toeplitz productT u T v ¯, with entire symbolsu andv, is bounded if and only ifu = e q, v = C e - q, whereq is a linear complex polynomial andC is a nonzero constant.